2005
DOI: 10.1353/sof.2005.0088
|View full text |Cite
|
Sign up to set email alerts
|

Familial and Religious Influences on Adolescent Alcohol Use: A Multi-Level Study of Students and School Communities

Abstract: A multi-level Durkheimian theory offamilial and religious influences on adolescent alcohol use is developed and tested with hierarchical linear modeling of data from Icelandic schools and students. On the individual level, traditional family structure, parental monitoring, paren tal support, religious participation, and perceptions of divine support and social constraint are associated with less adolescent alcohol use. Individual parents knowing other parents (intergenerational closure) is not associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 61 publications
2
51
0
5
Order By: Relevance
“…Catholics, by way of comparison, are less likely than Protestants to hold punitive attitudes, are less prone to the style of individualism associated with positive attitudes about guns, and some Catholics have connected pro-life attitudes with gun control (Bjarnason et al 2005;Froehle and Gautier 2000). The Catholic Church has an official stance on abortion, euthanasia, and capital punishment, whereas it has no official stance on guns.…”
Section: Find That Mainlinementioning
confidence: 99%
“…Catholics, by way of comparison, are less likely than Protestants to hold punitive attitudes, are less prone to the style of individualism associated with positive attitudes about guns, and some Catholics have connected pro-life attitudes with gun control (Bjarnason et al 2005;Froehle and Gautier 2000). The Catholic Church has an official stance on abortion, euthanasia, and capital punishment, whereas it has no official stance on guns.…”
Section: Find That Mainlinementioning
confidence: 99%
“…Baron and Hannan, 1994;Edwards and Foley, 1998;Morgan and Sorensen, 1999;Portes, 1998Portes, , 2000Woolcock, 1998), the theoretical issues originally raised under the banners of social capital theory were in fact fairly specific. Social capital theory seeks to strike a balance between undersocialized (Granovetter, 1985) and oversocialized (Wrong, 1961) conceptions of the social actor by emphasizing social emergence through the interplay of norms, networks, and social closure (Bjarnason et al, 2005). Coleman (1988) in particular sees social capital as a resource that inheres in the structural relations among individuals and groups.…”
Section: The Social Context Of Migration Expectations Among Adolescentsmentioning
confidence: 99%
“…For example, a recent study of undergraduates at a state university found that intrinsic religiousness, defined as the inner commitment to the moral and behavioral tenets of one's religion, was associated with less frequent alcohol use and lower average levels of alcohol consumption (Brown et al 2007). Among a sample of adolescents, Bjarnason et al (2005) found that the perception of divine support, the belief that God has provided, or would provide emotional support, was inversely associated with alcohol use. Such results hint at the potential gains from refining the conceptualization and measurement of religious factors that may constrain or deter health-risk behaviors.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 99%